Prognosis and Complications of Attempted Suicidal Hanging - Azadeh Memarian (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Background: Hanging is a form of strangulation, in which the body is suspended through the neck and the weight of the body acts as a constricting force. This study assessed various factors on the outcome of hanging and identification of prognostic factors related to the outcomes. Methods: Ninety-nine hanging victims from 1995 to 2015 in Iran were evaluated; then, variables such as the cause of death, distribution of mortality, duration of hospitalization, substance abuse consumption, respiratory distress, and cerebral edema were studied in these people. Finally, the data were analyzed. Results: Major cases of suicide by hanging were men. In connection with prognosis, about 12% of the deaths occurred in men and about 21% were represented in women. More importantly, in the matter of suspension, the model was largely incomplete to complete. Also, the outcomes of pulmonary stress and cerebral edema were recognized in association with the type of hanging and mortality prognosis. Conclusion: Only two risk factors, including loss of consciousness at the time of entry into the medical center, as well as the complete suspension, would be predictive operations of death and unsuccessful revival.